PP-077 Therapeutic education in childhood asthma: impact on disease control - Fatma, Khalsi; Asma, Marzouk; Aisha, Turki; Asma, Bouaziz; Khedija, Boussetta (BMJ paediatrics open, 2024)
AimAssess the control of asthma and the knowledge of parents of children with asthma about asthma after therapeutic education session.Material and MethodThe study was conducted at the Department of Pediatrics and Neonatology at the Regional Hospital of Ben Arous. It included 35 patients aged 6 to 15 years, who had been diagnosed with asthma for at least 3 months. Following a collective education session led by a multidisciplinary team, data were collected using pre-tests and post-tests spaced three months apart. These assessments evaluated knowledge about asthma using the AAKQ questionnaire and disease control using the Asthma Control Test (ACT).ResultsThe study involved parents, with 80% being mothers, the majority of whom had primary or secondary education. Approximately 51% of them were over 35 years of age. Sixty-nine percent of the children were exposed to passive smoking, and the same percentage had a family history of atopy. The average age of the patients was seven and a half years. Skin tests were performed in 86% of the children, with positive results in 49% of cases. The educational session significantly impacted parents’ knowledge, increasing the average AAKQ score from 35.9 to 53.9 (p<0.001). Comparative analysis of ACT scores before and after the educational session demonstrated significant improvement in all patients, with the ACT score increasing from 17.29 to 22 (p<0.001). Success factors for the therapeutic education session were identified, highlighting the crucial role of parental involvement and a family history of atopy. Improvement in asthma control and parental knowledge was not influenced by their educational level.ConclusionsThis study underscores the significance of therapeutic education in enhancing asthma management in school-aged children. Family history of atopy can play a key role in parental engagement and their understanding of the disease.